Increasing Cooperative Excellence Through Revitalization Strategy - Sri Djatnika Sya'diah (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Cooperatives as an important economic institution in Indonesia play a strategic role in improving the members’ welfare and contributing to the national economy. However, challenges such as low member participation, weak managerial competencies, and competition with other financial institutions remain problems that must be overcome. The digital era, marked by advances in digital technology, brings new challenges and opportunities for cooperatives. This research aims to review literature related to cooperative revitalization strategies to increase the advantages of cooperatives in the digital era. This research uses secondary data collected by evaluating findings from previously published research. Data collection was carried out by selecting journals that met the criteria, including journals that had been accredited by SINTA in the last 10 years and had gone through critical assessment using the critical appraisal method. The results show that cooperatives need to innovate, improve management, and provide digital literacy training to survive and develop in this era. A decrease in the number of active cooperatives requires revitalization efforts that include organizational changes, strengthening regulations, digital marketing, product innovation, and more efficient human resource management. In this Internet of Things and digital era which is influenced by advances in digital technology, revitalizing cooperatives is a must.